Theoretical Substantiation of the Angle of Mounting a Flat Ridge-Forming Disc of a Row Crop Cultivator - Zykin Evgeny (EDP Sciences, 2021)
The authors have developed a row-crop cultivator equipped with a ridge former, which allows performing high-quality operations of row crop cultivation in one pass. The inter row cultivation is carried out with a row-crop cultivator, on each section of which two ridge formers are mounted so that their flat discs are directed towards the row of plants at an acute angle, and the extreme edges of the wings of the V-shaped sweeps are located at the lower base of the soil ridge. When the row-crop cultivator moves, the V-shaped sweeps loosen the soil to the required depth and cut the weeds, and the flat discs move the soil layer coming off the wings of the V-shaped sweeps towards the rows of plants, hilling them and burying the weeds. In the presented article, the authors theoretically substantiate the angle of attack of a flat disc for burying weeds with a layer of soil of the required thickness. It was found that the angle of attack depends on the radius of the flat disc and the depth of its movement in the soil, the initial dimensions of the ridge and the physical and mechanical properties of the soil.